Credit counseling: a substitute for consumer financial literacy? - Disney, Richard; Gathergood, John; Weber, Jörg (Cambridge University Press, 2015)
Is financial literacy a substitute or complement for financial advice? We analyze the decision by consumers to seek financial advice in the form of credit counseling. Credit counseling is an important component of the consumer credit sector for consumers facing debt problems. Our analysis accounts for the endogeneity of an individual's financial situation to financial literacy, and the endogeneity of financial literacy to exposure to credit counseling. Results show counseling substitutes for financial literacy. Individuals with better literacy are 60% less likely to use credit counseling. These results suggest that credit counseling provides a safety net for poor financial literacy.